A transcriptional activator from Rhizophagus irregularis regulates phosphate uptake and homeostasis in AM symbiosis during phosphorous starvation - Zhang, Shuyuan; Nie, Yuying; Fan, Xiaoning; Wei, Wei; Chen, Hui; Xie, Xianan; Tang, Ming (Frontiers in Microbiology, 2023)
Phosphorus (P) is one of the most important nutrient elements for plant growth and development. Under P starvation, arbuscular mycorrhizal (AM) fungi can promote phosphate (Pi) uptake and homeostasis within host plants. However, the underlying mechanisms by which AM fungal symbiont regulates the AM symbiotic Pi acquisition from soil under P starvation are largely unknown. Here, we identify a HLH domain containing transcription factor RiPho4 from Rhizophagus irregularis. To investigate the biological functions of the RiPho4, we combined the subcellular localization and Yeast One-Hybrid (Y1H) experiments in yeasts with gene expression and virus-induced gene silencing approach during AM symbiosis. The results indicated that RiPho4 encodes a conserved transcription factor among different fungi and is induced during the in planta phase. The transcription of RiPho4 is significantly up-regulated by P starvation. The subcellular localization analysis revealed that RiPho4 is located in the nuclei of yeast cells during P starvation. Moreover, knock-down of RiPho4 inhibits the arbuscule development and mycorrhizal Pi uptake under low Pi conditions. Importantly, RiPho4 can positively regulate the downstream components of the phosphate (PHO) pathway in R. irregularis. In summary, these new findings reveal that RiPho4 acts as a transcriptional activator in AM fungus to maintain arbuscule development and regulate Pi uptake and homeostasis in the AM symbiosis during Pi starvation.